Edward M. Curr and the Tide of History - Furphy, Samuel (ANU Press, 2013)
Edward M. Curr (1820-89) was a pastoralist, horse trader, stock inspector, Aboriginal administrator, author and ethnologist. A prominent figure in the history of the Colony of Victoria, he rose to a senior position in the public service and authored several influential books and essays. He is best remembered for his nostalgic memoir, Recollections of Squatting in Victoria (1883), which has become a standard historical source. This book is the first comprehensive biography of Curr and explores both his life and legacy. In particular, it considers his posthumous influence on the Yorta Yorta native title case (1994-2001), when his written account of the Yorta Yorta ancestors played a key role in the failure of the claim. By exploring Curr's interactions with Aboriginal people-as a pastoralist and Aboriginal administrator-this book advocates a more nuanced, critical, and historically informed interpretation of Curr's ethnological writings than was evident in the Yorta Yorta case.